REVIEW DAN ANALISIS PERKEMBANGAN PLTS PADA SARANA TRANSPORTASI LAUT - Made Puji Dwicaksana; I Nyoman Satya Kumara; I Nyoman Setiawan; I Made Aditya Nugraha (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2021)
This paper aims to review the current development of vessels with solar power to reference the research and development of solar power vessels in Indonesia. The research method is a systematic literature review on the development of solar-powered vessels and includes an online survey of vessels using solar PV. This study found 86 solar-powered vessels consisting of boats, utility boats, ferries, houseboats, research, vehicle carriers, dive boats, and yachts developed from 1988 to 2020. These solar-powered vessels were built for various functions such as competitions, cleaning the environment, passenger transportation, and water tourism.  Production of solar-powered vessels is increasing in terms of production volume, PV capacity, and battery capacity. In terms of PV configuration, the solar array is dominated by a fixed array structure. However, there have been innovations using sun-tracking, wind tracking airfoils, and expandable channels to increase PV capacity.